A study of double-layered wall and prism deflector to improve natural ventilation in a confined space - Mohamed Arifin, Yusmady; Akop, Mohd Zaid; Lai, Tak Oon; Ewe, Tek Bee; Tee, Boon Tuan; Shamsudin, Shamsul Anuar (Universiti Teknikal Malaysia Melaka (UTeM), 2015)
Natural ventilating and cooling strategies need to be considered as a substitute to the present air conditioning system. However, the effectiveness of the natural air ventilation in providing cooler environment still needs further investigation. This study proposed a new method, using a double-layered wall and a prism deflector to improve air ventilation in a confined space. Experimental and simulation approaches were used in this study. The results yielded that the double-layered wall and prism deflector configuration can be used to improve air ventilation in the confined space. The significant effect of the prism deflector was dependent on the combination of parameters used. The use of a 45 hole angle inner wall, and a higher prism deflector ratio were able to enhance the air ventilation more effectively.